Synthesis and optical properties of 1-naphthol rhodamine for deep red laser dyes. Issue 39 (25th September 2020) - Ming, Wei; Chen, Fan; Hu, Xiaojie; Zhang, Zhizhong; Chang, Shunzhou; Chen, Risheng; Tian, Baozhu; Zhang, Jinlong
Abstract: In this study, we synthesized two asymmetric rhodamine laser dyes based on 1-naphthol (Dye-1 and Dye-2) and investigated their photophysical and laser performances. It was found that the fluorescence emission wavelengths of the two dyes are successfully extended to the deep red region. Compared with Dye-1, the esterification product Dye-2 displays a redshift of ∼8 nm in the maximum absorption wavelength ( λ abs ) and fluorescence emission wavelength ( λ em ). In aprotic solvents, both λ abs and λ em of Dye-2 red-shift with the increase of solvent polarity, while its fluorescence quantum yield always decreases with the increase of solvent polarity, no matter in protic solvents or aprotic solvents. The results of laser tests indicated that both Dye-1 and Dye-2 have wide laser tuning range and strong laser conversion efficiency in the red region. The laser conversion efficiency is closely relative to the dye concentration and linearly increases with the increase of pump laser energy. Graphical abstract: Leave this area blank for abstract info. Image 1 Highlights: Two rhodamine laser dyes based on 1-naphthol were synthesized for the first time. Both of the two dyes display a wide laser tuning range. Both of the two dyes exhibit a strong laser conversion efficiency in the deep red region. Solvents have a vital influence on both the laser conversion efficiency and laser stability.